The use of artificial intelligence in a military context: development of the attitudes toward AI in defense (AAID) scale - Hadlington, Lee; Binder, Jens; Gardner, Sarah; Karanika-Murray, Maria; Knight, Sarah (Frontiers in Psychology, 2023)
Although the use of artificial intelligence (AI) applications for national security considerations is a matter of high societal significance and ongoing public discourse, very little is known about public acceptance or rejection of AI in military contexts. In particular, there is no current measure of attitudes available for this specific context while more general attitudinal measures on AI use are unlikely to capture relevant perceptions and opinions.A measure was therefore developed for the assessment of Attitudes towards AI in Defence (AAID) in the form of an item scale in questionnaire format. The present work describes the process of instrument design and subsequent piloting and refinement. A representative sample of the adult population in the UK (n = 1,500) was utilised for item analysis and selection and for establishing psychometric properties. The resulting final AAID scale consists of 15 items distributed over two factors and is suitable for use on studies involving the general public.